2016
DOI: 10.1177/0193945916682953
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Parental HPV Knowledge and Intentions to Have Their Daughters Vaccinated

Abstract: Human papillomavirus (HPV) 16 and 18 causes 66% of cervical cancers (Dunne et al., 2014). Vaccination during adolescence can prevent HPV-associated cervical cancers, yet less than half of adolescent girls are vaccinated. This study examined the association between HPV knowledge and parental intentions to vaccinate daughters against HPV. A retrospective, cross-sectional, national data set from the 2006-2007 Health Information National Trends Survey (HINTS) was used. A multivariate multinomial logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
2
5
0
2
Order By: Relevance
“…Having said this, published studies in the United States showed that improving the knowledge levels of parents had no effect on vaccination willingness [ 67 ]. However, other studies in the United States have shown a strong positive association between knowledge regarding the HPV vaccine and willingness to have their children vaccinated, similar to studies in Nigeria and Thailand [ 68 , 69 , 70 ]. On a positive note, 94% of the respondents in our study were interested in obtaining more information, and this desire for more information is an opportunity for increasing HPV vaccine uptake.…”
Section: Discussionsupporting
confidence: 68%
“…Having said this, published studies in the United States showed that improving the knowledge levels of parents had no effect on vaccination willingness [ 67 ]. However, other studies in the United States have shown a strong positive association between knowledge regarding the HPV vaccine and willingness to have their children vaccinated, similar to studies in Nigeria and Thailand [ 68 , 69 , 70 ]. On a positive note, 94% of the respondents in our study were interested in obtaining more information, and this desire for more information is an opportunity for increasing HPV vaccine uptake.…”
Section: Discussionsupporting
confidence: 68%
“…35 Moreover, several studies among different groups showed that the knowledge of HPV infection was associated with the willingness to vaccinate their children. 8,36,37 It should be noted that among the sociodemographic characteristics, only marital status resulted significantly associated with the vaccine hesitancy, since those unmarried were more likely to be hesitant. This observation may be explained by the fact that the mothers, without the support of the husbands, might have difficulty in vaccinations' choice and, therefore, be more hesitant.…”
Section: Discussionmentioning
confidence: 99%
“…The US failed to achieve the Healthy People 2020 target of 80% HPV vaccination coverage. Given the associations between HPV-related awareness and HPV vaccination uptake, 14 , 15 efforts must be geared toward addressing the declining awareness of HPV and HPV vaccine observed at the population level. While further studies are needed to unravel the underlying factors responsible for observed declines in HPV-related awareness within the general US population and specified sociodemographic groups, robust public health efforts must be undertaken to reverse ongoing trends and the negative impact it may have on HPV vaccination coverage.…”
Section: Discussionmentioning
confidence: 99%
“…14 Another study found that parents who had HPV knowledge were more likely to have intentions to allow HPV vaccination than those who were not knowledgeable about HPV. 15 Studies show that a majority of the US population are aware of HPV and HPV vaccine, [16][17][18] yet severe knowledge gaps continue to exist surrounding the more salient HPV-related details. For example, a study found that more than 60% of US women did not know if the HPV vaccine was successful in cancer prevention.…”
Section: Introductionmentioning
confidence: 99%